2020
DOI: 10.2147/ott.s235951
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification of Novel lncRNA Markers in Glioblastoma Multiforme and Their Clinical Significance: A Study Based on Multiple Sequencing Data</p>

Abstract: Background: Long non-coding RNAs (lncRNAs) have been verified to have a vital role in the progression of glioblastoma multiforme (GBM). Our research was about to identify the potential lncRNAs which was closely associated with the pathogenesis and prognosis of glioblastoma multiforme. Methods: All RNA sequence profiling data from patients with GBM were obtained from The Genotype-Tissue Expression (GTEx) and The Cancer Genome Atlas (TCGA). Differently expressed genes identified from GBM and control samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…Normalized RNA-seq data with the estimation of Fragments Per Kilobase of exon model per Million mapped fragments (FPKM) of glioblastoma patients and the corresponding clinical information were acquired from TCGA database ( https://portal.gdc.cancer.gov/ , RRID: SCR_003193). The exclusion criteria were as follows: 1) samples with unknown survival information; 2) samples with OS less than 30 days, who died because of nonneoplastic factors, such as myocardial infarction, hemorrhage, and severe infection ( Cheng et al, 2015 ; Li and Guo, 2020 ). A total of 151 TCGA glioblastoma samples were included for the subsequent analysis, that were randomly split up into the training set and the validation set.…”
Section: Methodsmentioning
confidence: 99%
“…Normalized RNA-seq data with the estimation of Fragments Per Kilobase of exon model per Million mapped fragments (FPKM) of glioblastoma patients and the corresponding clinical information were acquired from TCGA database ( https://portal.gdc.cancer.gov/ , RRID: SCR_003193). The exclusion criteria were as follows: 1) samples with unknown survival information; 2) samples with OS less than 30 days, who died because of nonneoplastic factors, such as myocardial infarction, hemorrhage, and severe infection ( Cheng et al, 2015 ; Li and Guo, 2020 ). A total of 151 TCGA glioblastoma samples were included for the subsequent analysis, that were randomly split up into the training set and the validation set.…”
Section: Methodsmentioning
confidence: 99%
“…Through survival package [17], univariate cox regression analysis was presented for screening prognosis-related genes in the hypoxia-relevant coexpression module in TCGA dataset. A LASSO prognostic model was then established utilizing glmnet package [4]. Using survival package, risk score was determined in line with the expression value and LASSO regression coefficient of each candidate gene.…”
Section: Construction Of a Least Absolute Shrinkage And Selectionmentioning
confidence: 99%
“…Patients who develop GBM have the median survival rate of <1 year and high death risks [2]. Numerous studies have developed genomic models for risk stratification and prognosis prediction of GBM [4][5][6]. Nevertheless, because of technical problems such as limited sample size and individual heterogeneity, most models possess limited reproducibility and none of them have been applied in clinical routine practice.…”
Section: Introductionmentioning
confidence: 99%
“…10 RNF144A-AS1 was also identified in glioblastoma multiforme and served as a potential lncRNA biomarker. 11 However, only a few studies have reported its role in BC progression. One report suggested RNF144A-AS1 as a prognostic factor for BC using the least absolute shrinkage and selection operation Cox regression.…”
Section: Introductionmentioning
confidence: 99%